1997
DOI: 10.1097/00000372-199704000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Spiradenoma and Dermal Cylindroma: Comparative Immunohistochemical Analysis and Histogenetic Considerations

Abstract: We carried out an immunohistochemical analysis of nine spiradenomas and seven cylindromas. Our findings underscore the histomorphological similarities of the two adnexal neoplasms-namely, the expression of S-100 protein ascribed to eccrine differentiation within the tubular and large, pale-staining cells of both entities. Human milk fat globulin (HMFG) and lysozyme, two markers associated with apocrine differentiation, are expressed by tubular cells in spiradenomas and cylindromas. Lysozyme is also expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
3
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 40 publications
1
34
3
2
Order By: Relevance
“…Our specimen also displayed these distinctive histological features with two types of cells in the tumor nodule. Several previous studies have reported the expression of the immunohistochemical marker S-100, suggesting a relationship with neural tissue [18,19,20]. S-100 protein is normally present in cells derived from the neural crest (Schwann cells, melanocytes and glial cells), chondrocytes, adipocytes, myoepithelial cells, macrophages, Langerhans cells, dendritic cells and keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Our specimen also displayed these distinctive histological features with two types of cells in the tumor nodule. Several previous studies have reported the expression of the immunohistochemical marker S-100, suggesting a relationship with neural tissue [18,19,20]. S-100 protein is normally present in cells derived from the neural crest (Schwann cells, melanocytes and glial cells), chondrocytes, adipocytes, myoepithelial cells, macrophages, Langerhans cells, dendritic cells and keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous theories have been suggested as to the question of whether they are apocrine or eccrine origin [2,6]. Meybehm and Fischer [22] performed an immunohistochemical analysis of nine spiradenomas and seven cylindromas. They report that the two lesions present histomorphological similarities to adnexal structures and which can be evidenced by the immunohistochemical expression of S-100, lysozyme, alpha-smooth muscle actin, and cytokeratin staining patterns including keratins 7, 8, and 18 [22].…”
Section: Discussionmentioning
confidence: 99%
“…Meybehm and Fischer [22] performed an immunohistochemical analysis of nine spiradenomas and seven cylindromas. They report that the two lesions present histomorphological similarities to adnexal structures and which can be evidenced by the immunohistochemical expression of S-100, lysozyme, alpha-smooth muscle actin, and cytokeratin staining patterns including keratins 7, 8, and 18 [22]. Other markers indicating derivation from both eccrine and apocrine glands include positive reactivity to EMA, CEA, mucinlike carcinoma-associated antigen (b12), laminin, collagen IV, fibronectin, and CD34.…”
Section: Discussionmentioning
confidence: 99%
“…Der Nachweis von "ekkrin-typischen" Enzymen wie Phosphorylase oder Succinatdehydrogenase gelang bei Spiradenomen nur vereinzelt [7,14] und misslang bei Zylindromen [20]. Interessanterweise zeigten direkt vergleichende immunhistochemische Studien an Zylindromen und Spiradenomen mehr Übereinstimmungen in den Färbemustern als Unterschiede: So konnten bei beiden Tumorarten sowohl S-100-Protein, karzinoembryonisches Antigen (CEA) und "Gross cystic disease fluid protein-15", alle typisch für eine ekkrine Differenzierung, als auch Lysozym und "human milk factor globulin", typisch für eine apokrine Differenzierung, "a smooth muscle actin", typisch für sezernierende Zellen, und zusätzlich nahezu identische Zytokeratinmuster nachgewiesen werden [9,16,21,30]. Zusammenfassend erbrachten die histologischen, elektronenmikroskopischen, enzymatischen und immunhistologischen Untersuchungen keinen eindeutigen Beweis, inwieweit die Tumoren primär apokrinen oder ekkrinen Ursprunges sind.…”
Section: Histogenetische Einteilung Von Zylindromen Und Spiradenomenunclassified
“…ekkrin differenzierten Ursprung zuordnen zu wollen. Man erkennt zunehmend, dass beide Tumoren aus ähnlich heterogen differenzierten Zellen bestehen, die fokal in unterschiedlichem Ausmaß Eigenschaften von apokrinen oder ekkrinen, duktalen oder sezernierenden oder auch basaloiden Zellen aufweisen können [21]. Aufgrund dieser Heterogenität lässt sich spekulieren, dass sich Zylindrome und Spiradenome aus pluripotentem Epithel entwickeln.…”
Section: Bedeutung Verschiedener Faktoren Im Hinblick Auf Den Differeunclassified